Study on Rib Sloughage Prevention Based on Geological Structure Exploration and Deep Borehole Grouting in Front Abutment Zones - Cheng Wang; Zuqiang Xiong; Chun Wang; Yuli Wang; Yaohui Zhang (Geofluids)
This research presents the grouting method of preventing rib sloughage which severely impacts mine safety and longwall retreat speed in thick coal seam with numerical simulation and laboratory tests. Based on the analysis of the plastic failure mode of five types of coal seam, roof strata ahead of the longwall face, and fractures developed in the coal seam, the following results are drawn, the range and degree of plastic failure generated in the coal seam and roof strata ahead of the longwall face gradually decreased as the coal mass strength increased; the grouting boreholes are essentially laid out within the coal rib instead of the roof. For a particular case of a coal mine in Shanxi province, a novel cement-based material was grouted, which fulfilled the reinforcement requirements under the tectonic stress regions and front abutment zones. Besides, the grouting borehole construction requested predrilled boreholes, full borehole intubation, lengthened hole sealing, and multiple-step drilling and grouting. This study can provide a theoretical framework of a design overview and practical basis for similar mining conditions in other coalfields.